The Influence of Non-Physical Work Environment, Job Rotation, Demographic Characteristics on Career Development and Employee Work Achievement Kota Bima Health Department - Syahrul, Syahrul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Career development and employee work performance is not just a coincidence, but many factors influence it, namely the work environment, job rotation and demographic characteristics. The aim of this research is to determine the influence of the non-physical work environment, work rotation, demographic characteristics on career development and work performance of Bima City Health Service Employees. This research uses associative research methods. The sample in this study amounted to 42 people. The instrument used in the research was a questionnaire. Data were analyzed using multiple regression with the SPSS program. Based on the research results, it can be concluded that the non-physical work environment, work rotation, and demographic characteristics have a significant influence on the career development and work performance of Bima City Health Service Employees